Three-dimensional magnetotelluric modeling in general anisotropic media using nodal-based unstructured finite element method. (March 2021) - Ye, Yixin; Du, Jiaming; Liu, Ying; Ai, Zhengmin; Jiang, Fenyong
Abstract: Magnetotelluric sounding is an efficient and economical method for detecting Earth's deep structure because of its large surveying depth. We use a finite element approach to solve magnetotelluric fields in three-dimensional general anisotropic media based on the vector–scalar potentials and unstructured meshes. The implementation of a three-dimensional unstructured mesh generator TetGen with high-quality local mesh refinement can easily handle complicated models with high performance. The electromagnetic field equations are expressed in terms of Coulomb-gauged vector–scalar potentials, and the nodal-based finite element method can be used to compute the electromagnetic fields with high efficiency. The symmetric successive over-relaxation preconditioned conjugate gradient solver is used to solve the resulting linear equation system. The magnetotelluric responses in one-, two-, and three-dimensional medias are computed through our proposed approach. These results are then compared with the analytical solutions, two- and three-dimensional adaptive finite element solutions. Numerical examples demonstrate that these results are in good agreement. Because an unstructured mesh is incorporated in this approach, it has great potential for simulating the magnetotelluric responses in geometrically complicated situations. Highlights: 3D MT modeling considering full anisotropy using nodal-based FE method is presented. The MT responses of a 3D model with real topography is simulated. The performance of unstructured mesh with local mesh refinement is high. The use of nodal-based FE method has fewer unknowns than the vector FE method.